Cigarette expenditures among poor households in Indonesia in 2007 and 2014 (based on IFLS data) - Rahayu, Meyi Setiawati; Hasanbasri, Mubasysyir; Dasuki, Djaswadi (BKM Public Health and Community Medicine, 2021)
Purpose: This study aims to analyze cigarette expenditures among poor households and examine whether economic status, chronic diseases, health insurance ownership, and demographic factors influence these expenditures. Methods: This study employs a quantitative research design with a cross-sectional approach, utilizing secondary data from the Indonesia Family Life Survey (IFLS) conducted in 2007 and 2014. The criteria for the respondents are poor families, smokers, and age > 15 years old, with a sample of 1,243 respondents (2007) and 1,549 respondents (2014). Results: In 2007, cigarette expenditure was influenced by low economic status (OR = 3.34), interest in health insurance (OR = 1.10), age, sex, and place of residence, while a history of chronic disease and education level had no effect. In 2014, economic status and health-related factors no longer had a significant impact; however, age (OR = 2.45) and gender (OR = 0.54) remained influential, with no effect observed from education or residence. Conclusion: Economic status and demographic factors are key determinants of high cigarette expenditures among poor families in Indonesia. Monthly spending on cigarettes remains relatively high, and many poor households still lack health insurance. The government is expected to strengthen awareness and policies related to smoking, particularly those concerning health and health insurance for the poor.